The Influence of Irradiation and Accelerated Aging on the Mechanical and Tribological Properties of the Graphene Oxide/Ultra-High-Molecular-Weight Polyethylene Nanocomposites - Guodong Huang; Zifeng Ni; Guomei Chen; Yongwu Zhao (International Journal of Polymer Science)
Graphene oxide/ultra-high-molecular-weight polyethylene (GO/UHMWPE) nanocomposite is a potential and promising candidate for artificial joint applications. However, after irradiation and accelerated aging, the mechanical and tribological behaviors of the nanocomposites are still unclear and require further investigation. GO/UHMWPE nanocomposites were successfully fabricated using ultrasonication dispersion, ball-milling, and hot-pressing process. Then, the nanocomposites were irradiated by gamma ray at doses of 100 kGy. Finally, GO/UHMWPE nanocomposites underwent accelerated aging at 80°C for 21 days in air. The mechanical and tribological properties of GO/UHMWPE nanocomposites have been evaluated after irradiation and accelerated aging. The results indicated that the incorporation of GO could enhance the mechanical, wear, and antiscratch properties of UHMWPE. After irradiation, these properties could be further enhanced, compared to unirradiated ones. After accelerated aging, however, these properties have been significantly reduced when compared to unirradiated ones. Moreover, GO and irradiation can synergistically enhance these properties.